2022
DOI: 10.1002/jsfa.12288
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of evaporated soymilk prepared in the laboratory using normal and 11S‐lacking soybean seeds

Abstract: BACKGROUND Soymilk is utilized not only as a beverage but also as an alternative to bovine milk, including products such as yoghurt and cream. Evaporated soymilk is expected to be utilized as condensed milk. Raw and heated soymilk samples prepared in our laboratory were evaporated and then subjected to viscosity measurement. The soymilk samples were made from two different varieties: Fukuyutaka, which contains 7S and 11S globulin proteins; and an 11S‐lacking soybean (Nanahomare). RESULTS Raw Fukuyutaka soymilk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The intense bands observed around the molecular weights of 50 000 and 70 000 are considered to be the β subunit and the α and α′ subunits of 7S globulin, respectively 27 . The bands observed around 23 and 36 kDa are considered to be the basic and acidic polypeptides derived from 11S globulin, respectively 2 . In the samples with a pH of 4.3 and 4.9 (Nos.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intense bands observed around the molecular weights of 50 000 and 70 000 are considered to be the β subunit and the α and α′ subunits of 7S globulin, respectively 27 . The bands observed around 23 and 36 kDa are considered to be the basic and acidic polypeptides derived from 11S globulin, respectively 2 . In the samples with a pH of 4.3 and 4.9 (Nos.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean is generally composed of about 40% protein, and thus soymilk has a high protein content. 1,2 In addition, soymilk is low in fat and has no cholesterol, making it a nutritional and healthy drink. Furthermore, a systematic review and meta-analysis revealed that consumption of soymilk might have beneficial effects on cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soymilk was prepared following a previously described method with minor modification (Shimoyamada et al, 2015, 2022). A 30 g of soybeans were washed twice with distilled water and soaked in distilled water for 13 h in a refrigerator at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Soymilk was prepared following a previously described method with minor modification (Shimoyamada et al, 2015(Shimoyamada et al, , 2022. A 30 g of soybeans were washed twice with distilled water and soaked in distilled water for 13 h in a refrigerator at 4 C. The hydrated soybeans were then mixed with 210 g of distilled water, including absorbed water, and this mixture was homogenized using a homogenizer (SX10; Mitsui Electric Co., Ltd., Noda, Japan) for 8 min at 10,000 rpm.…”
Section: Raw Soymilk Preparationmentioning
confidence: 99%